Indirekt blodtrycksmätning på katt : påverkan av metod, miljö och ålder - Andersson, Emma (SLU/Dept. of Animal Environment and Health (until 231231), 2007)
The purpose of the present study was to study if the systemic blood pressure in cats significant increases due to stress associated with a visit to a veterinarian clinic. We also wanted to investigate the clinical utility of two different methods for indirect blood pressure measurements in cats by assessing how easy they were to use and how reliable measurements they provided. The methods that were used were oscillometric (Memo Diagnostic) and ultrasound-doppler technique (Minidop). The blood pressure was measured in both clinical environment and home environment. Fifty cats were used in the study, from which measurements were impossible to obtain in one cat. Twelve cats were uncooperative and it was not possible to obtain five measurements with each device in these cats. However, These cats were included in the statistic analyses, because only three readings were stipulated in the study protocol. The blood pressure in cats was systematically higher at the clinic compared to values obtained at home. The difference was most prominent for the systolic blood pressure obtained with the oscillometric device (P=0,02). This difference was, presumably, not great enough to be of clinical importance (MV osc clinic 137/75 mmHg, doppler clinic 119; MV osc home 131/71, doppler home 114). A significant difference between systolic blood-pressure measurements was found between the two different methods. The doppler-technique showed significantly lower values. A statistic significant association between age and raised systolic blood pressure was found (P<0,0001). The blood pressure increased with increasing age. Environment, equipment and age had significant effect on the blood pressure in cats. The doppler device were considered more difficult to use and more frequently provided unrealistic measurements. Presumably, this was caused by operator inexperience and lack of training. The oscillometric method was considered easier to use and was generally tolerated better by the cats.